Jaminan Produk Makanan Halal Pedagang Kaki Lima di Kawasan Religi Sunan Ampel Perspektif Undang-Undang No. 33 Tahun 2014 - Fikri Abdillah Maulana; A'rasy Fahrullah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The Sunan Ampel religious area is one of the places labeled as halal tourism in Indonesia, especially in Surabaya. Halal tourism is a vehicle or entertainment for the community in which there are religious elements from tombs to entertainment venues with an Islamic atmosphere. Of course halal tourism must guarantee the halalness of the entire halal tourism area, from location to consumption products. Halal in Indonesia has been regulated by the government through laws to government regulations and clerical fatwas. Law No. 33 of 2014 is one of the regulations that contains matters relating to halal certification and regulates the obligation of halal certification for macro and micro businesses throughout Indonesia. Street vendors are included in micro businesses that should be mandatory for halal certification, but according to observation data and observations made at street vendors in the Sunan Ampel religious area, there are still many street vendors who do not understand or do not understand halal certification. As evidenced by the ingredients that are still vague because they do not know the clarity of the ingredients used, starting from the unclear slaughter process, naming products that still contain kufr and falsehood, the hygiene of some traders that has not been guaranteed in accordance with the rules of the existing regulations in Law. No. 33 of 2014 and regulations relating to halal certification. Keywords Halal Product Guarantee, Street Food, Ampel Sunan Religious Area, Law No. 33 of 2014, halal certification.